Clinicopathological features in anterior visual pathway in neuromyelitis optica. Issue 4 (22nd February 2016) - Hokari, Mariko; Yokoseki, Akiko; Arakawa, Musashi; Saji, Etsuji; Yanagawa, Kaori; Yanagimura, Fumihiro; Toyoshima, Yasuko; Okamoto, Kouichirou; Ueki, Satoshi; Hatase, Tetsuhisa; Ohashi, Riuko; Fukuchi, Takeo; et al.
Abstract : Objective: Neuromyelitis optica spectrum disorder (NMOsd) is an autoimmune disorder of the central nervous system characterized by aquaporin‐4 (AQP4) autoantibodies. The aim of this study was to elucidate the characteristics of involvement of the anterior visual pathway (AVP) and neurodegeneration via glia–neuron interaction in NMOsd. Methods: Thirty Japanese patients with serologically verified NMOsd were assessed with a neuro‐ophthalmological study. Using 27 tissue blocks from 13 other cases of NMOsd, we performed neuropathological analysis of glial and neuroaxonal involvement in the AVP. Results: The AVP involvement in NMOsd was characterized by the following, compared to multiple sclerosis: (1) longitudinally extensive optic neuritis (ON); (2) more severe visual impairment and worse prognosis for ON; (3) unique AQP4 dynamics, including loss of AQP4 immunoreactivity on astrocytes with complement activation in ON lesions, loss of AQP4 immunoreactivity on Müller cells with no deposition of complement in the retinas, and densely packed AQP4 immunoreactivity on astrocytes in gliosis of secondary anterograde/retrograde degeneration in the optic nerves and retinal nerve fiber layer (RNFL); and (4) more severe neurodegeneration, including axonal accumulation of degenerative mitochondria and transient receptor potential melastatin 4 channel with complement‐dependent astrocyte pathology in ON lesions, mild loss of horizontal cells, and RNFL thinning and loss of ganglion cells with abundance of AQP4 + astrocytes, indicating secondary retrograde degeneration after ON. Interpretation: Severe and widespread neuroaxonal damage and unique dynamics of astrocytes/Müller cells with alterations of AQP4 were prominent in the AVP and may be associated with poor visual function and prognosis in NMOsd. Ann Neurol 2016;79:605–624